The Gap Between Local Multiplier Algebras of C ∗ -algebras∗ - Argerami, Martin (2009)
The local multiplier algebra Mloc(A) of a C*-algebra A has the property that Mloc (A) ⊆ Mloc(Mloc(A)). In this paper we show that there is a separable liminal C*-algebra A such that the inclusion is proper.